Philosophy of biology - Matthen, Mohan; Stephens, Christopher, 1967 June 4- (Handbook of the philosophy of science., 2007)
Philosophy of Biology is a rapidly expanding field. It is concerned with explanatory concepts in evolution, genetics, and ecology. This collection of 25 essays by leading researchers provides an overview of the state of the field. These essays are wholly new; none of them could have been written even ten years ago. They demonstrate how philosophical analysis has been able to contribute to sometimes contested areas of scientific theory making.-Written by internationally acknowledged leaders in the field - Entries make original contributions as well as summarizing state of the art discoveries in the field - Easy to read and understand.